2013
DOI: 10.1080/00206814.2013.774156
|View full text |Cite
|
Sign up to set email alerts
|

Long-lived Neoproterozoic high-K magmatism in the Pernambuco–Alagoas Domain, Borborema Province, northeast Brazil

Abstract: The Pernambuco-Alagoas (PE-AL) Domain contains major granitic batholiths typified by a wide range of T DM model ages (Archaean to Neoproterozoic), reflecting the important role of quartzofeldspathic plutons attending the Brasiliano (Pan-African) Orogeny. U/Pb zircon data for eight syn-to post-collision to syn-transcurrent granitic intrusions of the PE-AL Domain allow the studied plutons to be divided into two groups: (1) granitoids with crystallization ages older than 600 Ma (Água Branca, Serra do Catú, Serra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 54 publications
(86 reference statements)
1
4
0
7
Order By: Relevance
“…The age of 615 Ma falls within the age range of 632e606 Ma estimated for the peak of metamorphism contemporaneous with thrusting in the Central and Pernambuco-Alagoas domains (Neves et al, 2006b. It is also similar within errors to the ages of intrusion of syn-orogenic calc-alkaline granitoids in the Pernambuco-Alagoas and Central domains (624e616 Ma; Guimarães et al, 2011;Neves et al, 2012;Da Silva Filho et al, 2013) and in the Sergipano Belt (628e625 Ma;Long et al, 2005;Bueno et al, 2009). It seems therefore that in the whole eastern portion of the Borborema Province a change from (Boynton, 1984).…”
Section: From Extension To Shortening: Onset Of the Brasiliano Orogenymentioning
confidence: 62%
“…The age of 615 Ma falls within the age range of 632e606 Ma estimated for the peak of metamorphism contemporaneous with thrusting in the Central and Pernambuco-Alagoas domains (Neves et al, 2006b. It is also similar within errors to the ages of intrusion of syn-orogenic calc-alkaline granitoids in the Pernambuco-Alagoas and Central domains (624e616 Ma; Guimarães et al, 2011;Neves et al, 2012;Da Silva Filho et al, 2013) and in the Sergipano Belt (628e625 Ma;Long et al, 2005;Bueno et al, 2009). It seems therefore that in the whole eastern portion of the Borborema Province a change from (Boynton, 1984).…”
Section: From Extension To Shortening: Onset Of the Brasiliano Orogenymentioning
confidence: 62%
“…Granitoids of the 640-620 Ma age range are significantly present in the Transverse, Pernambuco-Alagoas, and Sergipano domains of the Borborema Province, which is the Brazilian equivalent for the CAFB (Galindo et al 1995;Van Schmus et al 2008Guimarães et al 2011. In a recent study of the Buique-Paulo Alfonso and Áqua Belas-Canindé batholiths outcropping in the Pernambuco-Alagoas Domain, Silva Filho et al (2013) reported the occurrence of granites that range in age from 612 ± 7 to 624 ± 5 Ma. Similar ages have been reported for the Sitios Novos and Coronel João Sá granitoid Plutons (Silva Filho et al 1997), as well as the granitic rocks occurring along the Belo Monte Jeremoabo and Macururé Shear Zones (Araújo et al 2004) within the Sergipano Domain.…”
Section: 24mentioning
confidence: 97%
“…Os dados geocronológicos disponíveis para o magmatismo shoshonítico no Sul da Província Borborema (e.g., Guimarães et al, 2004;Brito et al, 2009;Silva Filho et al, 2013Ferreira et al, 2015;Lima, 2016;Lisboa et al, 2019) sugerem que a colocação desses corpos está relacionada ao evento de colisão e que eles são intrusivos em dois momentos distintos da evolução do arco vulcânico (Silva Filho et al, 2013;Lisboa et al, 2019).…”
Section: Discussionunclassified